Ionotropic glutamatergic receptors in the rostral medullary raphe modulate hypoxia and hypercapnia-induced hyperpnea - Nucci, Tatiane B.; Dias, Mirela Barros; Branco, Luiz G. S.; Gargaglioni, Luciane H. [UNESP] (Elsevier B.V., 2011)
It has been suggested that the medullary raphe (MR) plays a key role in the physiological responses to hypoxia and hypercapnia. We assessed the role of ionotropic glutamate receptors in the rostral MR (rMR) in the respiratory responses to hypoxia and hypercapnia by measuring pulmonary ventilation (V(E)) and body temperature (Tb) of male Wistar rats before and after microinjecting Kynurenic acid (KY, an ionotropic glutamate receptors antagonist, 0.1 mM) into the rMR followed by 60 min of hypoxia (7% O(2)) or hypercapnia exposure (7% CO(2)). Compared to the control group, the ventilatory response to hypoxia was attenuated in animals treated with KY intra-rMR, however the ventilatory response to hypercapnia increased significantly. No differences in Tb among groups were observed during hypoxia or hypercapnia. These data suggest that the glutamate acting on ionotropic receptors in the rMR exerts an excitatory modulation on hyperventilation induced by hypoxia but an inhibitory modulation on the hypercapnia-induced hyperpnea. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ventilation; Raphe; Glutamate; Hypoxia; Hypercapnia